P106 Evaluating the correlation between objective daytime sleepiness, daytime functioning and subjective sleepiness. (7th October 2021) - Chee, A; Lim, P; Lee, A; Narayan, L; Zhang, T; Capomolla, T; Suthers, B; Paech, G
Abstract: Introduction: Daytime sleepiness is typically assessed in clinical settings with the Multiple Sleep Latency Test (MSLT) and Maintenance of Wakefulness Test (MWT). However, these tests do not necessarily assess daytime functioning. This study aimed to assess the correlation between a 10-min Psychomotor Vigilance Test (PVT), as a measure of daytime functioning, and excessive daytime sleepiness as measured with the MSLT or MWT. Methods: Patients attending the sleep clinic for assessments of daytime sleepiness underwent overnight polysomnography (PSG) and completed the Epworth Sleepiness Scale (ESS). The following day, patients completed four test sessions every 2h starting 1.5h after waking. Testing sessions included the Stanford Sleepiness Scale (SSS), PVT, MWT or MSLT. PVT lapses (reaction time >500ms), SSS score and sleep latencies (MSLT and MWT) were averaged within participants across sessions and regression analyses performed to assess the relationship between PVT lapses and sleepiness measures. Results: A total of 41 patients (BMI: 33.7±8.7kg/m²; aged 44.8±17.8 years) completed the study. Of these, 22 (19 F) underwent the MSLT and 19 (2 F) underwent the MWT. PVT lapses correlated with MWT mean sleep latency (r²=0.62; p<0.001), ESS (r²= 0.19; p<0.01) and SSS (r²= 0.12; p<0.05) but not MSLT mean sleep latency (r²= 0.02; p = 0.50). Discussion: In clinical practice, MWT and ESS are often used in conjunction to assess daytime functioning. Results suggest that the PVT could be used alongside MWT to aid clinical judgments around an individuals' daytime functioning.